(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Customer loyalty has a very important role in ensuring the continuity of a company, especially in the daily necessities retail sector. One of the leading daily needs retail businesses in Denpasar City is Tiara Dewata Supermarket, which now has to face intense competition with similar businesses. One of the customer loyalty is influenced by the store atmosphere. The purpose of this study was to determine the effect of store atmosphere on customer loyalty either directly or through customer satisfaction as a mediating variable. This research was conducted at Tiara Dewata Supermarket located in Denpasar City by involving 100 respondents based on calculations using the Slovin formula and using a purposive sampling technique, accidental sampling. Primary data collection is done by conducting interviews and questionnaires. The measurement scale used is a Likert scale with five answer choices and the data analysis technique used is path analysis with Sobel test to test the role of customer satisfaction as a mediating variable. The results of the study prove that store atmosphere has a positive and significant effect on customer satisfaction and customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, and customer satisfaction mediates the influence of store atmosphere on customer loyalty.